Neuro-ophthalmology - Thurtell, Matthew J.; Tomsak, Robert L. ([New York] : Oxford University Press, 2019)
Part of the'What do I do now?' series,'Neuro-Ophthalmology' uses a case-based approach to cover common and important topics in the examination, investigation, and management of afferent (visual), efferent (eye movement), eyelid, pupil, and orbital disorders. Each chapter provides a discussion of the diagnosis, key points to remember, and selected references for further reading. For this edition, all cases and references have been updated and several new cases have been added.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 8, 2019).
Keywords: Neuroophthalmology; Eye -- Diseases -- Diagnosis; Nervous system -- Diseases -- Diagnosis; Neuroophthalmology -- Case studies